The Development of JA32211 Supplementary Course on Exploring a World of Japanese Reading to Develop Japanese Language Reading Comprehension Using CIRC Technique with Graphic Organizer of Grade 11 Students - Seti, Kanokporn; Art-In, Dr.Sitthipon (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
The objectives of this research were: 1) to develop JA32211 Supplementary Courses on Exploring a World of Japanese Reading to Develop Japanese Language Comprehension. 2) to study the efficiency of the teaching. 3) to study the satisfaction with learning. The target group was 15 students in grade 11 at Pathumthep Witthayakarn School. The research design was Research and Development. There were 5 research instruments: 1) the interview 2) the requirement 3) supplementary course 4) the lesson plans 5) the test 6) the satisfaction. The results were summarized: 1) The overall rating scale of the JA32211 Supplementary Course was very good criterion (= 4.82, S.D. = 0.41) 2) To study the results of JA32211 Supplementary Course student reached the Japanese Reading Comprehension score at an average of 22.27 which is equivalent to74.33percent. 3) The students’ satisfaction through CIRC technique with Graphic organizer reached good criterion (= 4.48, S.D. = 0.61)